Learning Difficulties in Beginning Reading for Elementary School Students - Cholifah, Nurul; Sutama, S (Universitas Muhammadiyah Surakarta, 2023)
Reading skills in the early grades play an important role as the basis or foundation for successful academic activities. However, there are still many students who need help learning to read. The research to analyzing the difficulties of beginning reading. To describe the factors that cause learning difficulties in beginning reading. To explain solutions that can be used in overcoming learning difficulties in beginning reading. This research uses qualitative research methods with phenomenological design. The place and time of the research was Tungalsari II State Elementary School, Surakarta Indonesia. The subjects of this research were teachers, guardians, and second-grade students. A credibility test was used to test the validity of the data obtained. Data collection techniques through observation, interviews, and documentation. Data analysis technique with flow method. The results showed that students' difficulties in beginning reading are recognizing letters, not being able to string syllables, and so on. Factors that influence learning difficulties in beginning reading, namely: lack of student interest in learning, lack of parental attention, and so on. Alternative solutions to early reading difficulties include; teachers holding additional hours for students who still have difficulty learning to read, teachers paying special attention to students who have difficulty reading, and so on. In this research reveals the factors and alternative solutions used by teachers in overcoming elementary school students' reading learning difficulties.